Explaining Decentralization Performance in Indonesia: Member of Parliament Decision, Political Networks, and Constitution Amendment - Baidhowah, Adfin (Research and Development Agency Ministry of Home Affairs, 2022)
Decentralization has several positive impacts on Indonesian local government performance. To date, many studies have unpacked the positive implications of Indonesian decentralization. Yet, few have shown a structural argument of the decentralization reform trajectory in Indonesia constitutional reform 1998-2002. This study investigates the dynamic processes of parliament voting within the constitution amendment on the decentralization article as a source of the existing Indonesian decentralization performance. Analyzing research questions will conduct; to what extent do political networks shape the content of the decentralization article in the constitution amendment in 1999-2000; how much pressures out of parliament session affect the political networks within Indonesian constitution amendment the decentralization article. This study applies a theory that social networks and personal relations sourced from party alignment can explain the outcome variations of decisions at the political arenas. The quantitative method is used to construct independent variables of political networks in testing to what extent informal political networks influence the voting of members of parliament within 32 meetings in 1999 and 2000. In presenting statistical, empirical findings, this study points out that the constitutional amendment, which ‘produces’ new decentralization article, is a direct result of bargaining between members of parliament, which builds informal political networks. So, this provision creates an improved performance of Indonesian decentralization today. Due to the statistical, empirical findings talking to wider themes of parliament and decentralization, this study suggests paying more attention to the indicators of political networks on and off parliament’s formal meetings within the constitution amendment.